Correlations between frailty index and inflammatory markers derived from blood cell count in the United States - Shaojie Han; Zenghui Zhang; Siyuan Cheng; Yuchen Han; Qianyun Wang; Yangbo Xi; Panpan Li; Fengjuan Li; Jun Guo (BMC Public Health)
Abstract Background Complete blood cell count (CBC)-derived inflammatory biomarkers are crucial indicators of adverse outcomes and possess predictive value for a wide range of diseases. The objective of this study was to evaluate the links between CBC-derived inflammatory biomarkers and frailty index. Methods Information was gathered from the National Health and Nutrition Examination Survey (NHANES) spanning the years 1999 to 2016. The research investigated the correlation between inflammatory biomarkers derived from CBC, including the neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR), systemic inflammatory response index (SIRI), and systemic immune-inflammation index (SII), and Rockwood’s frailty index, using logistic regression analyses. Results In total, the cross-sectional study involved 13,507 U.S. adults aged 50 and older, with 3,729 individuals (24%) meeting the criteria for frailty. After adjusting for confounding factors, elevated levels of logNLR (odds ratio [OR] 3.45, 95% confidence interval [CI] 2.52–4.73), logMLR (OR 3.58, 95% CI 2.44–5.25), logSIRI (OR 2.77, 95% CI 2.17–3.55), and logSII (OR 1.89, 95% CI 1.44–2.48) were significantly associated with an increased frailty index in the entire study population. We also found that frailty index and inflammatory biomarkers derived from CBC have a non-linear relationship by restricted cubic spline. Conclusions Our findings indicate a correlation between frailty index and NLR, MLR, SIRI, and SII among elderly adults. Considering their wide accessibility in both clinical and laboratory practice, these biomarkers may be recommended as potential indicators for the development of frailty.